Bangla number plate recognition from noisy video footage using deep learning - Chowdhury, Mahfuzur Rahman; Shahriar, MD. Muyeed; Meem, Esrat Jahan; Hossain, S.M.Faiyaz (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2020.